Dual-modality imaging with combined scanners 2 - Beyer, Thomas (Henry Stewart Talks, 2010)
Advances in PET(/CT) technology, Time-of-flight PET, Novel PET/CT system designs, Advances in CT technology, Patient and staff exposure, Imaging guidelines: PET/CT and SPECT/CT, PET/MR or PET/CT?, PET/MR design considerations, Pre-clinical imaging using dual-modality scanners
Updated at 2021/03/15